Periclimenes macrorhynchia sp. nov., a new hydrozoan-associated pontoniine shrimp (Crustacea, Decapoda, Palaemonidae) from North East Kalimantan, Indonesia - Eilbracht, Joni; Fransen, Charles H.j.m. (Zootaxa, 2015)
A new species of pontoniine shrimp belonging to the ‘Periclimenes obscurus species group’ is described from the Berau Islands, North East Kalimantan, Indonesia. Specimens were obtained from aglaopheniid hydrozoans of the genus Macrorhynchia. The new species is here described and figured. Its affinities with related species are discussed and a DNA-barcode is provided.